MARCH8 Restricts RSV Replication by Promoting Cellular Apoptosis Through Ubiquitin-Mediated Proteolysis of Viral SH Protein - Okura, Takashi; Takahashi, Tatsuki; Kameya, Taichi; Mizukoshi, Fuminori; Nakai, Yusuke; Kakizaki, Masatoshi; Nishi, Mayuko; Otsuki, Noriyuki; Kimura, Hirokazu; Miyakawa, Kei; Shirato, Kazuya; Kamitani, Wataru; et al. (Viruses, 2024)
Numerous host factors function as intrinsic antiviral effectors to attenuate viral replication. MARCH8 is an E3 ubiquitin ligase that has been identified as a host restriction factor that inhibits the replication of various viruses. This study elucidated the mechanism by which MARCH8 restricts respiratory syncytial virus (RSV) replication through selective degradation of the viral small hydrophobic (SH) protein. We demonstrated that MARCH8 directly interacts with RSV-SH and catalyzes its ubiquitination at lysine 13, leading to SH degradation via the ubiquitin-lysosomal pathway. Functionally, MARCH8 expression enhances RSV-induced apoptosis through SH degradation, ultimately reducing viral titers. Conversely, an RSV strain harboring the SH-K13R mutation exhibited prolonged SH protein stability and attenuated apoptosis in infected cells, even in the presence of MARCH8. Targeted depletion of MARCH8 enhances cellular survival and potentially increases viral persistence. These findings demonstrate that MARCH8 promotes the early elimination of virus-infected cells by abrogating the anti-apoptotic function of SH, thereby reducing viral transmission. Our study provides novel insights into the interplay between host restriction factors and viral evasion strategies, potentially providing new therapeutic approaches for RSV infections.